Determination of heavy metal accumulation in fish species in Galas River, Kelantan and Beranang Mining Pool, Selangor - Baharom, Zarith Sufiani; Ishak, Mohd Yusoff (Elsevier, 2015)
Concentrations of heavy metals namely Cu, Zn, Pb, Ni, Mn and Cd were detected in tissue of six freshwater fish species (Hampala microlepidota, Barbonymus schwanenfeldii, Mystacoleucus marginatus, Hemibagrus nemurus, Cyclocheilicthys apogon and Oreochromis niloticus from Galas River and Beranang mining pool. The samplings were carried out from June to November 2014. Heavy metals in fish were analyzed by Inductively Coupled Plasma- Mass Spectrometry (ICP-MS) and Atomic Absorption Spectrophotometer (AAS). Irrespective of fish species, range for muscle samples are Zn> Ni>Cd>Cu>Mn>Pb. Levels of Zn and Pb in the tilapia muscle from mining pool were higher than fish from Galas river. M. marginatus, H. macrolepidota and B. schwanenfeldii showed highest concentration for Mn, Cu and Ni. The range for heavy metals in Galas river are Zn>Mn>Pb>Ni>Cu. Concentrations of heavy metals in water samples and fish were lower than permissible limit set by Food Act 2003 and Malaysian Food Regulations 1983